Nature and uses of fluorescent dyes for drug transporter studies. (August 2015) - Fardel, Olivier; Le Vee, Marc; Jouan, Elodie; Denizot, Claire; Parmentier, Yannick
<x xml:space="preserve">Abstract</x> Introduction: Drug transporters are now recognized as major players involved in pharmacokinetics and toxicology. Methods for assessing their activity are important to consider, particularly owing to regulatory requirements with respect to inhibition of drug transporter activity and prediction of drug–drug interactions. In this context, the use of fluorescent-dye-based transport assays is likely to deserve attention. Areas covered: This review provides an overview of the nature of fluorescent dye substrates for ATP-binding cassette and solute carrier drug transporters. Their use for investigating drug transporter activity in cultured cells and clinical hematological samples, drug transporter inhibition, drug transporter imaging and drug transport at the organ level are summarized. Expert opinion: A wide range of fluorescent dyes is now available for use in various aspects of drug transporter studies. The use of these dyes for transporter analyses may, however, be hampered by classic pitfalls of fluorescence technology, such as quenching. Transporter-independent processes such as passive diffusion of dyes through plasma membrane or dye sequestration into subcellular compartments must also be considered, as well as the redundant handling by various distinct transporters of some fluorescent probes. Finally, standardization of dye-based transport assays remains an important on-going issue.